Controlled Layer-By-Layer Deposition of Carbon Nanotubes on Electrodes for Microbial Fuel Cells - Wenguo Wu (Energies, 2019)
Carbon nanotubes (CNTs) and polyelectrolyte poly(allylamine hydrochloride) (PAH) composite modified indium tin oxide (ITO) electrodes, by a layer-by-layer (LBL) self-assembly technique, was evaluated as an anode for microbial fuel cells (MFCs). The bioelectrochemistry of Shewanella loihica PV-4 in an electrochemical cell and the electricity generation performance of MFCs with multilayer (CNTs/PAH)n-deposited ITO electrodes as an anode were investigated. Experimental results showed that the current density generated on the multilayer modified electrode increased initially and then decreased as the deposition of the number of layers (n = 12) increased. Chronoamperometric results showed that the highest peak current density of 34.85 ± 2.80 mA/m2 was generated on the multilayer (CNTs/PAH)9-deposited ITO electrode, of which the redox peak current of cyclic voltammetry was also significantly enhanced. Electrochemical impedance spectroscopy analyses showed a well-formed nanostructure porous film on the surface of the multilayer modified electrode. Compared with the plain ITO electrode, the multilayered (CNTs/PAH)9 anodic modification improved the power density of the dual-compartment MFC by 29%, due to the appropriate proportion of CNTs and PAH, as well as the porous nanostructure on the electrodes.